Community support for sex offender rehabilitation in Europe - Höing, Mechtild A.; Petrina, Romulus; Hare Duke, Laurie; Völlm, Birgit; Vogelvang, Bas (Sage, 2016)
It is assumed that the public holds negative attitudes towards sex offenders, yet an increasing number of European volunteers are involved in sex offender rehabilitation programmes through Circles of Support and Accountability (CoSA). Public attitudes and their correlates have been mainly studied in Anglo-Saxon countries; research in European countries other than the UK is scarce. To fill this gap, a web-based survey was held among web-panels in nine European countries (n = 200 per country). Measures included awareness and knowledge about sex offenders, community attitudes towards sex offenders in the community (CATSO), attitudes towards the treatment of sex offenders (ATTSO), public attitudes towards sex offender rehabilitation (PATSOR), support for CoSA, and attitudes towards volunteers working with sex offenders. Results indicated that clear misperceptions were held by a minority. Attitudes tended to be negative, but not extremely, and differences between countries were significant. The amount of support for CoSA was considerable and mean attitudes towards volunteers working with sex offenders were positive. The lower educated held more negative attitudes. Since webpanels were probably not representative on key demographic markers, the results are only indicative. Professionals should especially address the lower educated, correct key misperceptions about recidivism of sex offenders, and provide information about processes of change in convicted sex offenders